THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON PROFITABILITY AND COMPANY VALUE - Aurora Angela; Vinny Stephanie Hidayat; Oktavianti Oktavianti (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
This study aims at determining the effect of CSR disclosure on profitability and company value. This study uses the population of all companies included in the LQ45 group listed on the IDX for three consecutive years, namely 2017, 2018, and 2019. The technique to test the hypothesis is Simple Linear Regression Analysis. It is used to determine the effect of CSR disclosure on profitability and the effect of CSR disclosure on company value.The result of this study is the disclosure of CSR does not have a significant effect on profitability neither does it affect the company value. Despite the fact that the results show that CSR disclosure does not have a significant effect, the authors suggest that companies continue carrying out CSR activities because it is a long-term investment activity.